(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the validity and reliability of a tool designed to assess nurses’ knowledge and practice in caring for pediatric patients with External Ventricular Drainage (EVD). Methods: A cross-sectional descriptive study was conducted from September 1, 2024, to June 30, 2025, involving 30 nurses at the Departments of Intensive Care and Neurosurgery, Children’s Hospital 2. The tool was developed by the research team and reviewed by six experts for content validity. The Scale-level Content Validity Index (S-CVI) was used to assess content validity. Exploratory Factor Analysis (EFA) was employed to identify underlying factor structures. Internal consistency was assessed using Cronbach’s alpha. Reliability was determined by calculating the Intraclass Correlation Coefficient (ICC) between two raters and Pearson’s correlation coefficient through test–retest on the same subjects. Results: Both the knowledge and practice questionnaires achieved S-CVI = 1. The knowledge questionnaire extracted 8 factors explaining 81.77% of total variance; Cronbach’s alpha was 0.70; ICC was 0.75 (p < 0.001); and Pearson’s r was 0.61 (p < 0.005). The practice questionnaire extracted 8 factors explaining 84.46% of total variance; Cronbach’s alpha was 0.81; ICC was 0.72 (p < 0.001); and Pearson’s r was 0.74 (p < 0.001). Conclusion: The tool demonstrated good validity and reliability, and is suitable for application in clinical practice and nursing research in the Vietnamese context.